2009 Association for the Sociology of Religion Presidential AddressCan Post-Secular Society Tolerate Religious Differences? - Dillon, Michele (Sociology of religion, 2010)
Amidst the visibility of religion in everyday culture and in political and civic debates, Jurgen Habermas's recent construal of post-secular society offers an intriguing shift in his approach to the accommodation of religion in the public sphere. The post-secular society is one that recognizes the relevance of religious ideas and intuitions in informing civic discourse and contributing to remedying the social pathologies of modernity. This paper welcomes Habermas's recent religious turn, but it also underscores some of the challenges and limits religion poses to its civic accommodation. The active tolerance of, and reflexive engagement with, religion required of post-secular society unearths several tensions in how religion itself is understood and practiced, and in how western societies deal with religious and cultural Otherness. Moreover, while the state may appear as a neutral actor mediating religious-based civic disputes, it too is encrusted with culturally particular understandings of what is normal and normative.